Delving into the Manobo tribe's literary pieces and culture - Diansig, Jessabel Panggoy; Quijano, Gemima Masaya; Valdez, Roshyn Gyll Blanco; Monteza, Ana Mae (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2024)
Cultural values represent the core beliefs, norms, and practices that shape the identity and behavior of individuals within a specific community. Understanding these values is crucial for maintaining cultural heritage, fostering social cohesion, and promoting cross-cultural understanding. This study aimed to explore the influence of the Manobo's literary pieces from their tribes and their relation to cultural values, including language preservation as one way of preserving their culture. The researchers employed a cultural values framework to comprehend and examine its cultural values. This qualitative study utilized research corpora, which we collected and analyzed. The researchers collected five (5) literary genres of the Manobo tribe: Songs, Riddles, Proverbs, Stories, and poems. The significant findings revealed the values embedded in the Manobo literary pieces, which prove that they have a substantial impact on the Manobo community from their generation past to the next generation. Thus, the collected literary texts are well-founded from the cultural values depicting humility, strong faith, and patriotism. The significant findings revealed the values embedded in the Manobo literary pieces, which prove that they have a substantial impact on the Manobo community from their generation past to the next generation.